I love you, Stinky Face - McCourt, Lisa.; Moore, Cyd. (New York : Scholastic, 2004)
A mother and child discuss how the mother's love would remain constant even if her child were a stinky skunk, scary ape, or bug-eating green alien.
On board pages.
Keywords: Mother and child -- Juvenile fiction; Animals -- Juvenile fiction